Activity test of 2,6-bis-(2-furilidine) sikloheksanonecompound antibacterial towards resistence Staphyloccus aureus bacteria - Ismi Rahmawati; Iswandi Iswandi; Sardjiman Sardjiman (Jurnal Sains Dasar, 2014)
The data that have been obtained in Indonesia by using samples of clinical material from the hospital, Staphylocccus aureusis proved to be resistant to penicilin and methicillin, tetracyclin, oxacilin, gentamicin, erytromycin, chloramphenicol, and trimethrophrim-sulfemethoxazole. The high resistant inStaphylocccus aureus bacteria encourage efforts to find drugs that have antibacterial activity. Furfural and its derivates are known to have antibacterial activity. The purpose of this study was to obtain derivate of furfural compound 2,6-bis-(2’-furilidyn)-sikloheksanone, which is expected to have antibacterial activity against drug resistant bacteria Methicillin resistant Stapylococcus aureus (MRSA). 2,6-bis-(2’-furilidyn)-sikloheksanone synthesis was done with starting materials ofcyclohexanone (0,0121 mol)and furfural (0,0121 mol), using KOH 7,5% as catalys in the aquadest solvent. The purity test were carried out with melting distance test, thin layer chromatography, and gas chromatography. Structure elucidation was performed with mass spectrometer analysis, IR, and spectrophotometer, H1-NMR. The syntesis result is then tested for its antibacterial activity againts MRSA bacteria with diffusion method to determine the inhibition diameter. The result of this study showed that 2,6-bis-(2’-furilidyn)-cyclohexanone has been successfully synthesized with an average yield of 73,60% ±0,204. Re-crystallization resulting in pure compound base on its melting range (1,90C), TLC (one spot Rf= 0,33), and GC (100% area). The results of the chemical structure elucidation by mass spectrometry, IR spectrophotometerand H-NMR spectrometer line with the target compound. The synthesis result has antibacterial activity with average of inhibition diameter at a concentration of 3,959mM/ml= 27 mm.   Keywords:synthesis, analog of curcumin, antibacterial